Information Literacy and Critical Analysis in Translation in the Era of Artificial Intelligence (AI) - Benni Ichsanda Rahman Hz (Association of Language Teachers in Southeast Asia (ALTSA), 2026)
Artificial intelligence (AI) has been widely used in the field of translation in recent years. However, the use of AI in translation has been limited due to its limitations in handling cultural nuances, implicit meanings, and complex language structures. This study aims to analyse the meta-language awareness of English Language Education students in conducting critical analysis of translation since the emergence of AI. In addition, this study explores how students assess the accuracy and bias in AI translation results and the extent to which they are able to correct or improve the translation independently. This case study focuses on students' perspectives and viewpoints in understanding, evaluating, and critiquing the translation results produced by AI and how their critical analysis skills develop in the context of translation. The findings highlight that AI can serve as a valuable tool, but it should not be solely relied upon for tasks requiring deep linguistic understanding, particularly in academic, professional, and cross-cultural communication settings.